Analytical modeling and simulation of a multifunctional segmented lithium ion battery unimorph actuator. (11th December 2020) - Gonzalez, Cody; Ma, Jun; Frecker, Mary; Rahn, Christopher
Abstract: Lithium-ion batteries (LIBs) are able to achieve large deformation and high actuation force when using a unimorph configuration and a silicon composite anode. Distribution of charge to different segments allows for shape change with only small parasitic losses due to internal resistance. A unique attribute of LIB actuators are their ability to maintain actuation shape. The actuation mechanism also requires no power to be consumed to maintain the deformed shape. Segmenting the unimorph improves the customizability and allows for spatial variation of the unimorph parameters. Spatially varying the charge and thickness of the unimorph along the length improves the range of motion and complex shapes achievable by this design. Spatially varying the thickness of the unimorph specifically allows for improved blocked force and actuation force per volume. An analytical model is developed to predict several key actuator metrics. Free deflection is found for a variety of example cases. Blocked deflection and blocked force are also found using a novel modified equivalent end moment method. Actuation force is found using a combination of both the free deflection and blocked force equations herein developed. Euler–Bernoulli beam theory is used, including the effects of beam segmentation and curvature shortening. This model and a commercial finite element analysis simulation are compared and experimentally verified.